PENGARUH BRAND EXPERIENCE DAN PRODUCT QUALITY TERHADAP KEPUASAN KONSUMEN MELALUI KEPUTUSAN PEMBELIAN PADA PRODUK SEPEDA MOTOR HONDA DI KOTA PEKANBARU - Saputra Ramadhan Awal; Nursanti Aida; Musfar Firli Tengku (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine how much influence the things that affectPurchase Decision and Consumer Satisfaction on users of Honda MotorcycleProducts in Pekanbaru City. Primary data were collected using a questionnaireas an instrument and structured interviews were used as a complement in provingthe results of the study. This study uses 114 Honda motorcycle users in Pekanbaruas respondents with the Non-Probability Sampling technique. With the conditionthat you have a Honda Motorcycle vehicle product, are over 17 years old anddomiciled in Pekanbaru City. The method used by Explanatory Research is dataanalysis test, classical assumption test, hypothesis test, and path analysis as thedata testing flow and is assisted by SPSS version 25 application in terms of dataprocessing. The results of this study indicate that the Brand experience andProduct Quality variables have a significant effect on Purchase Decision andConsumer Satisfaction. Keywords: Brand experience, Product Quality, Purchase Decision, ConsumerSatisfaction.